(untitled) (Modern education and development, 2024)
работа художественного переводчика многогранна и многофункциональна. Она включает в себя не только профессионализм, огромный опыт, знание культуры и традиций своего языка, но также и культурные аспекты языка оригинала, его традиций, людей. Понять и прочувствовать атмосферу подлинника не всегда достаточно, нужно быть знакомым с творчеством автора, понимать его ценности и убеждения, умение создать эмоциональный эффект. В данной работе рассматриваются особенности, а также проблемы художественного перевода.the work of a literary translator is multifaceted and multifunctional. It includes not only professionalism, vast experience, knowledge of the culture and traditions of one’s language, but also the cultural aspects of the original language, its traditions, and people. Understanding and feeling the atmosphere of the original is not always enough; you need to be familiar with the author’s work, understand his values ​​and beliefs, and the ability to create an emotional effect. This work examines the features and problems of literary translation